Examining the effects of job demand, organizational support, and psychological capital on work-life balance and employee performance: A conceptual framework - Phiwphong, Kritsanapol; U-on, Vichit (Edelweiss Applied Science and Technology, 2025)
This conceptual paper aims to explore the effects of job demand, organizational support, and psychological capital on work-life balance and employee performance. Drawing from an extensive review of contemporary literature in organizational behavior and human resource management, the study synthesizes key theoretical perspectives and empirical findings to develop a causal framework that explains how these factors interact to influence employee outcomes. The model posits that excessive job demands negatively impact work-life balance and performance, while organizational support and psychological capital serve as critical enablers that enhance both work-life balance and performance. By articulating these relationships, the paper offers valuable insights for advancing theory and guiding practical interventions aimed at fostering employee well-being and optimizing organizational effectiveness.